2002
DOI: 10.1038/sj.onc.1205630
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 43, but not connexin 32, is mutated at advanced stages of human sporadic colon cancer

Abstract: The membrane-spanning connexin proteins form microscopic intercellular channels that directly connect the cytoplasms of adjacent cells and as such have been implicated in maintenance of tissue homeostasis. They are considered to act as tumor suppressors since their function or expression is frequently aberrant in tumor cells. Several mechanisms appear to be involved in this, but irreversible mutational alterations have not yet been proved to be among them. In this study we have demonstrated for the first time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
54
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 26 publications
2
54
1
Order By: Relevance
“…These frame-shift mutations result in the carboxyterminal domain truncated Cx43 expression, which is suggestive of the importance of CT-domain of Cx43 in growth regulation. The importance of Cx43 in colon cancer is evident from the studies indicating its frequent mutations and their correlation with the colon sporadic adenocarcinomas (Dubina et al, 2002). In fact, studies have shown that many proteins, involved in growth control interact with Cx43 at its CT domain (Giepmans, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…These frame-shift mutations result in the carboxyterminal domain truncated Cx43 expression, which is suggestive of the importance of CT-domain of Cx43 in growth regulation. The importance of Cx43 in colon cancer is evident from the studies indicating its frequent mutations and their correlation with the colon sporadic adenocarcinomas (Dubina et al, 2002). In fact, studies have shown that many proteins, involved in growth control interact with Cx43 at its CT domain (Giepmans, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…[1][2][3] Gap junctions are the only channels that allow direct exchange of small metabolites between cells. The building proteins of gap junction channels, connexins (Cx), constitute a family with as many as 20 distinct isoforms in mammals.…”
mentioning
confidence: 99%
“…Only one connexin gene mutation in human tumours has been described so far (advanced stages of human sporadic colon cancer) [26]. On the other hand, there is growing body of evidence suggesting that connexin genes could be inactivated by hypremethylation of their promoter regions [27].…”
Section: Discussionmentioning
confidence: 99%